Multifunctional catalyst VSA-CoNX and method for realizing coupled hydrogen production by using same
By using the hydrothermal method in water electrolysis technology, V-doped VSA-CoNX catalyst prepared as a cathode and anode, it solves the problem of slow kinetics of the anode oxygen evolution reaction, and achieves high-efficiency and low-cost hydroelectric hydrogen production , reducing energy consumption and production costs.
Patent Information
- Application Number
- CN202411474627.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-22
- Publication Date
- 2025-01-10
AI Technical Summary
In the existing water electrolysis technology, the kinetics of the anode oxygen evolution reaction are slow, resulting in low efficiency and high cost of electrolysis, and the risk of explosion in the high-voltage driving and efficient hydrogen production process.
The V-doped VSA-CoNX catalyst was prepared by hydrothermal method, and the multifunctional catalyst VSA-CoNX was formed by nitriding the V-Co(OH)2 precursor, which was used to work simultaneously as a cathode and anode in an anion exchange membrane electrolytic cell to achieve Coupled hydrogen production.
It improves the stability and performance of the catalyst, reduces the cost of hydrogen production, realizes efficient production of hydrogen at low voltages, and significantly reduces energy consumption and production costs.
Smart Images

Figure CN119287437A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of water electrolysis, and in particular to a multifunctional catalyst V SA -CoN X A preparation method thereof and a method for realizing coupled hydrogen production using the catalyst. Background Art
[0002] The decomposition of water to produce hydrogen and oxygen is considered to be one of the most promising ways to alleviate the energy crisis and environmental degradation problems. It includes two half reactions, hydrogen evolution reaction (HER) and oxygen evolution reaction (OER). Researchers have invested a lot of effort in developing efficient OER and HER catalysts. The precious metal Pt (Ru & Ir) is still the current benchmark catalyst for HER (OER) with excellent catalytic activity. However, the disadvantages of precious metal catalysts such as high price, low content and poor stability have seriously restricted their further commercial large-scale application. At the same time, the production of catalysts with multiple functions usually requires different equipment and synthesis processes, which greatly increases the investment cost. Therefore, designing a multifunctional catalyst with high catalytic activity at both the cathode and the anode in the coupled hydrogen production process is very important for reducing the cost of hydrogen production.
[0003] On the other hand, the main reason restricting the further development of green hydrogen is the high electricity price caused by the higher electrolysis voltage in the water electrolysis process. About 42% to 43% of the cost of hydrogen production by electrolysis of water comes from electricity. In addition, in general water electrolysis applications, the cathode HER is coupled with the anode OER to produce hydrogen. But compared with HER, due to the complex four-electron transfer process, OER is always slow, which leads to high voltage to drive efficient hydrogen production. Despite efforts to develop effective OER catalysts to reduce overpotential, the energy consumption of electrochemical water decomposition is still high. At the same time, the final product of OER, O2, is of low value and may explode when mixed with the H2 produced in the electrolyzer. Summary of the invention
[0004] The purpose of the present invention is to solve the problem of slow kinetics of anode oxygen evolution reaction (OER) in the prior art, resulting in low efficiency and high cost of water electrolysis, and to provide a multifunctional catalyst VSA-CoNX and a method for coupled hydrogen production using the catalyst. SA -CoN X , successfully prepared a multifunctional catalyst V with high stability and high performance SA -CoN X , and can realize the coupling of various anion exchange membrane electrolyzers to produce hydrogen, which has broad industrial application prospects.
[0005] In order to solve the above technical problems, the technical solution adopted by the present invention is as follows: a multifunctional catalyst VSA -CoN X The preparation method comprises the following steps: using a hydrothermal method to prepare V-Co(OH)2 from a metal vanadium source and a cobalt source, using V-Co(OH)2 as a precursor, nitriding the V-Co(OH)2 precursor, and preparing a multifunctional coupled hydrogen production catalyst V SA -CoN X .
[0006] Preferably, 0.1-10mmol Co(NO3)2·6H2O, 1-20mmol CH4N2O, 1-10mmol NH4F, 0.1-10mmol NH4VO3 and 10-50mL deionized water are mixed evenly, and then purified nickel foam (NF) is added, and the mixture is reacted at 100-250°C for 5-20h, and dried in a nitrogen atmosphere to obtain a V-Co(OH)2 precursor; the obtained V-Co(OH)2 precursor is placed in a tubular furnace, and sintered at 300-800°C under nitriding conditions for 1-5h to obtain a multifunctional catalyst V SA -CoN X .
[0007] Preferably, the nitrogen source of the nitriding conditions is one of melamine, dicyandiamide, urea and ammonia.
[0008] The present invention also provides a multifunctional catalyst V prepared by the above preparation method. SA -CoN X The catalyst has a V-doped CoN nanowire structure in morphology.
[0009] Based on the above multifunctional catalyst V SA -CoN X The present invention provides three coupled hydrogen production methods, which are as follows:
[0010] One of the methods for coupling hydrogen production is to combine the above multifunctional catalyst V SA -CoN X It acts as both cathode and anode catalyst in 1M KOH electrolyte to achieve V SA -CoN X Catalyst for hydrogen production by hydrolysis in electrolyzer.
[0011] The second method of coupling hydrogen production is to combine the above multifunctional catalyst V SA -CoN X As cathode and anode catalysts, the cathode electrolyte is 1M KOH and the anode electrolyte is 1M KOH + 0.5M urea, achieving V SA -CoN X The catalyst oxidizes urea at the anode and simultaneously couples the water electrolysis process at the cathode to produce hydrogen.
[0012] The third method of coupling hydrogen production is to combine the above multifunctional catalyst V SA -CoN X As cathode and anode catalysts, the cathode electrolyte is 1M KOH and the anode electrolyte is 1M KOH + 0.3M hydrazine to achieve V SA -CoN X The catalyst oxidizes hydrazine at the anode and simultaneously couples the process of hydrogen production by water electrolysis at the cathode.
[0013] Preferably, the multifunctional catalyst V SA -CoN X The catalytic temperature in the H-type electrolyzer is room temperature and the reaction area is 1 to 5 cm 2 ; The multifunctional catalyst V SA -CoN X The catalytic temperature in the anion exchange membrane electrolyzer is 70°C and the reaction area is 1 to 5 cm 2 .
[0014] The present invention also provides the multifunctional catalyst V SA -CoN X Application in coupled hydrogen production on anion exchange membrane electrolyzer.
[0015] The beneficial effects of the present invention are:
[0016] 1. In the present invention, the doping of metal V effectively optimizes CoN X The surface characteristics and catalytic performance of the catalyst, the hydrophilic / aerophobic surface characteristics maximize the catalytic surface area during the catalytic process and prevent bubble blockage; the rapid partial conversion of hydroxyl oxide species under alkaline high pressure conditions also provides abundant active sites for OER and UOR. Therefore, the multifunctional catalyst V prepared by the present invention has a V-doped CoN nanowire structure in morphology. SA -CoN X .
[0017] 2. Multifunctional catalyst V prepared by the present invention SA -CoN X It should be used in coupled hydrogen production, not only has excellent hydrogen evolution performance, but also shows excellent performance in oxygen evolution, urea oxidation, and hydrazine oxidation, and has multi-functional and multi-application coupled hydrogen production potential; V SA -CoN X The contact angle of bubbles in alkaline liquid is 163.75°; in the catalyst stability test, catalyst V SA -CoN XIn the complete water splitting OWS, it exhibits excellent ampere-level current stability; in the alkaline anode process, it promotes the generation of hydroxyl oxide species and inhibits the accumulation of hydroxyl oxide species, which also provides excellent catalytic performance for oxygen evolution and urea oxidation; Catalyst V SA -CoN X It also exhibited a high degradation rate in the hydrazine oxidation process, at 200 mA cm -2 At a current density of 1 cm 2 The catalyst has a degradation efficiency of more than 99% within 2 hours (hydrazine content is less than 5 ppb, in line with national wastewater discharge requirements). Moreover, the application of multiple variable (overall water splitting OWS, urea-assisted hydrogen production HER-UOR, hydrazine-assisted hydrogen production HER-HzOR) anion exchange membrane electrolyzer devices at 70°C also provides great possibilities for commercial applications.
[0018] 3. Multifunctional catalyst V in the present invention SA -CoN X It also shows excellent performance in coupled hydrogen production under multiple working conditions. In particular, when V SA -CoN X The anion exchange membrane water electrolysis (AEMWE) electrolyzer was assembled by coupling hydrazine as anode and cathode to generate an ampere-level current density (1A cm -2 ) only requires an ultra-low voltage of 0.21V to produce hydrogen, which means that the same amount of hydrogen produced by hydrazine-assisted AEMWE only requires 11.17% of the energy consumption of traditional water electrolysis, or only 0.506kWhNm -3 H2, effectively saving energy and significantly reducing the cost of hydrogen production to $0.11 per kilogram, significantly reducing the cost of hydrogen production. Moreover, experiments have shown that the degradation rate of hydrazine-containing electrolyte can exceed 95% within two hours, which also illustrates its excellent ability to degrade wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 Schematic diagram of the synthesis method of Example 1;
[0020] Figure 2 The SEM images of Example 1, the intermediate of Example 1, Comparative Example 1 and the intermediate of Comparative Example 1 are shown;
[0021] Figure 3 The SEM, TME, spherical aberration electron microscope and element distribution (mapping) diagram of Example 1;
[0022] Figure 4 is the XPS graph of Example 1;
[0023] Figure 5 Graphs showing the liquid contact angle and bubble contact angle of Example 1 and Comparative Example 1;
[0024] Figure 6 is the XRD pattern of Example 1;
[0025] Figure 7 is the synchrotron radiation X-ray absorption spectrum (XAFS) diagram of Example 1;
[0026] Figure 8 LSV curves of HER performance of Example 1, Example 2, and Example 3;
[0027] Fig. 9 The LSV diagrams of HER, OER, and OWS of Example 1, Comparative Example 1, and other standard samples, and the OWS stability test diagram of Example 1;
[0028] Fig.10 The SEM image, TEM image, HR-TEM image and element distribution (mapping) image after the HER reaction of Example 1;
[0029] Fig.11 The SEM image, TEM image, HR-TEM image and element distribution (mapping) image after the OER reaction of Example 1;
[0030] Fig.12 The LSV diagrams of UOR and HER-UOR of Example 1 and Comparative Example 1 and the stability test diagram of HER-UOR of Example 1 are shown;
[0031] Fig.13 Impedance spectra of Example 1 at different voltages in electrolytes containing and not containing urea;
[0032] Fig.14 This is the in-situ Raman test spectrum of Example 1;
[0033] Fig.15 The SEM image, TEM image, HR-TEM image and element distribution (mapping) image of Example 1 after the UOR reaction;
[0034] Fig.16 The LSV diagrams of HzOR and HER-HzOR of Example 1 and Comparative Example 1, the stability test diagram of HER-UOR of Example 1 and the related hydrazine degradation rate test diagram;
[0035] Fig.17 This is the UV-visible spectrum of the second round of testing in Example 1;
[0036] Fig.18 The SEM image, TEM image, HR-TEM image and element distribution (mapping) image of the HzOR reaction of Example 1;
[0037] Fig.19 1 is a performance test curve related to Example 1 in the AEMWE device;
[0038] Fig. 20 The response curve of Example 1 when inputting step current and voltage into the AEMWE device. DETAILED DESCRIPTION
[0039] The present invention will be further described below in conjunction with the accompanying drawings and specific embodiments.
[0040] Example 1 Multifunctional Catalyst V SA -CoN X Preparation of -1
[0041] Step (1), dissolving 11.8mmol Co(NO3)2·6H2O, 7.5mmol CH4N2O, 4mmol NH4F, and 0.3mmol NH4VO3 in 30ml deionized water, mixing well, adding purified nickel foam (NF), reacting at 120°C for 6h, and drying in a nitrogen atmosphere to obtain a V-Co(OH)2 precursor;
[0042] Step (2), placing the V-Co(OH)2 precursor obtained in step (1) in a tube furnace, and sintering at 500°C in an ammonia atmosphere for 2 hours to obtain the final multifunctional coupled hydrogen production catalyst V SA -CoN X , named V SA -CoN X -1 (except for the comparison with Examples 2 and 3, the others are not described for simplicity and are named V SA -CoN X ).
[0043] Example 2 Multifunctional Catalyst V SA -CoN X Preparation of -2
[0044] The preparation method of the catalyst in this embodiment is the same as that in embodiment 1, except that the hydrothermal temperature in this embodiment is 150°C to prepare the final catalyst V SA -CoN X , named V SA -CoN X -2.
[0045] Example 3 Multifunctional Catalyst V SA -CoN X Preparation of -3
[0046] The preparation method of the catalyst in this embodiment is the same as that in embodiment 1, except that the sintering temperature in this embodiment is 400°C, and the final catalyst V is prepared.SA -CoN X , named V SA -CoN X -3.
[0047] Comparative Example 1
[0048] The preparation method of the catalyst in this comparative example is the same as that in Example 1, except that no metal vanadium source is added in this comparative example to prepare the catalyst CoN X .
[0049] Material characterization and testing of the catalysts prepared in Examples 1-3 and Comparative Example 1
[0050] The results are attached Figure 1-20 As shown:
[0051] Figure 1 Multifunctional coupled hydrogen production catalyst V SA -CoN X Preparation process;
[0052] Figure 2 This shows that V doping can effectively reduce the agglomeration of catalysts;
[0053] Figure 3 Description, transmission electron microscopy (TEM) ( Figure 3 a) and the corresponding high-resolution HRTEM image ( Figure 3 b) Confirmed CoN X The phase was successfully synthesized, and the lattice fringes of 0.213 nm were closely related to CoN X The (200) crystal plane of the catalyst is matched. HAADF-STEM and electron energy loss spectroscopy (EELS) also confirmed the presence of elements N, V, and Co, with V atoms dispersed in the catalyst ( Figure 3 c). In addition, TEM-EDS mapping also shows that Co, V, and N are uniformly distributed in the nanorods ( Figure 3 d);
[0054] Figure 4 This indicates that V doping does not produce strong electronic interactions on the main phase of the catalyst, that is, V and CoN X The electronic interaction between them is not the reason for the enhanced catalyst activity;
[0055] Figure 5 Description, Example 1V SA -CoN X It has better hydrophilicity and gas repellency, which can not only maximize the active sites of the catalyst during the reaction, but also effectively prevent the formation of a large number of bubbles leading to bubble blockage;
[0056] Figure 6 Explanation, the X-ray diffraction (XRD) patterns of Example 1 and Comparative Example 1 ( Figure 6 a) shows that both samples correspond closely to the standard card JCPDS#15-0806, which indicates that no additional crystalline phase is formed during the doping process. However, a closer look at ( Figure 6 The enlarged area shown in b) shows that the X In comparison, V SA -CoN X The diffraction peak of the CoN nanostructured carbon nanotubes moves to a smaller angle, and as the X-ray angle increases, the offset range gradually increases. According to the Bragg diffraction formula, this means that V is successfully doped into the main CoN nanostructured carbon nanotubes. X phase and produced lattice expansion;
[0057] Figure 7 , the electronic structure and coordination environment of the catalyst were analyzed by X-ray absorption spectroscopy (XAS). Figure 7 a depicts Co foil, CoO, Comparative Example 1 CoN X Example 1V SA -CoN X Co K-edge XANES spectra of CoN X and V SA -CoN X The absorption edge of the Co K edge is located between Co foil and CoO, indicating that the state of Co lies between 0 and +2. X and V SA -CoN X The overlapped Co K-edge XANES spectrum also verifies that the electronic environment of the Co site is not significantly affected by V incorporation, which is consistent with the Co2p3 / 2XPS results. A similar conclusion can be drawn from the V K-edge XANES spectrum ( Figure 7 b), where comparison with standard samples (V foil, V2O3, VO2 and V2O5) shows that V SA -CoN X The valence state of V in is between +3 and +4. Figure 7 c and d show V SA -CoN X Co and V in R space k 3 FT of weighted EXAFS oscillations. About 1.46 and The main peaks at correspond to the first-layer coordination of Co-N and VN / O. SA -CoN X Observed in The obvious peak at , confirms the existence of Co-V bond, which is consistent with the It is worth noting that, compared with CoN without V doping, X Compared with the samples, V SA -CoN X The Co-N bond length in Significantly increased to This again proves that due to the incorporation of metal V, more unsaturated metal sites are formed, resulting in the X EXAFS fitting was also performed to identify the lattice expansion of the V SA -CoN X The coordination structure of Co atoms in Figure 7 e and f), the fitting parameters are shown in Table 1. X In contrast, due to V doping, V SA -CoN X The atomic distance of Co-N bond in Increase to CoN X The average coordination number of Co-Co in the sample is 4.5, while V SA -CoN X The average coordination number of Co-Co in the cations was reduced to 4.1, and 0.8 Co-V coordination bonds appeared. All these results indicate that metal V can replace CoN X Some of the Co atoms in the ionomer exist in the form of single atoms.
[0058] Table 1 Fitting parameters
[0059]
[0060] CN, coordination number; R, distance between absorber and backscatteratoms; σ 2 ,Debye-Waller factor to account for both thermal and structural disorders; Rfactor indicates the goodness of the fit.Fittingrange: Areasonable range of EXAFS fittingparameters:0.600 <S0 2 <1.000; CN>0; Rfactor<0.02.
[0061] Figure 8, explore the effect of different preparation conditions on the performance of the prepared catalyst (Example 1, Example 2, Example 3), it can be shown that the appropriate preparation conditions (preferably the hydrothermal temperature is 120 ° C, the calcination temperature is 500 ° C) is also the key to determine the performance of the catalyst; (measured potential and reversible hydrogen electrode (RHE) formula conversion: E RHE =E Hg / HgO +0.925. 1M KOH solution was used as the electrolyte at room temperature, and linear sweep voltammetry (LSV) was performed at 5mV s -1 The scan rate is recorded, and by default all LSV curves are corrected by 85% iR); the following tests are all tested using Example 1 unless otherwise specified.
[0062] Fig. 9 , Example 1, Comparative Example 1 and other standard samples performance test results show that whether it is HER ( Fig. 9 a) or OER( Fig. 9 b), V SA -CoN X Both showed the best performance, requiring only ∼36 mV and ∼335 mV overpotentials to achieve 10 mA cm-2 for HER. -2 and 50 mA cm for OER -2 The current density is V SA -CoN X When used as cathode and anode to form an electrolyzer for all-water hydrogen separation, only 1.636 V of potential is required to reach 50 mA cm -2 The current density ( Fig. 9 c), and also has excellent catalytic stability ( Fig. 9 d); (Linear scanning conditions and Figure 8 same).
[0063] Fig.10 Explanation, for Example 1V SA -CoN X The catalyst material was characterized and analyzed after the HER stability test. From the SEM, TEM and HR-TEM images before and after the test, the sample V obtained in Example 1 after the stability test was SA -CoN X The type and distribution of elements had negligible effects, confirming the stability of this catalytic material;
[0064] Fig.11This indicates that, unlike HER, after the long-term stability test of OER, an obvious nanosheet region appeared at the edge of the original nanowire of the catalyst. This nanosheet region should be the high-valent Co species (CoOOH) formed in situ during the high-voltage stability test. The lattice constant corresponding to CoOOH also confirms this observation. EDS analysis shows that the element species did not change before and after stabilization;
[0065] Fig.12 The performance test results of Example 1 and Comparative Example 1 show that when 0.5 M urea is added to the electrolyte, Example 1 only needs a potential of 1.363 V to reach 50 mA cm -2 The current density of the reaction was reduced by 202 mV compared with the potential without urea addition. Fig.12 a). At the same time, Example 1V SA -CoN X When used as cathode and anode to form an electrolyzer for urea-assisted coupled hydrogen evolution, only a potential of 1.450 V is required to reach 50 mA cm -2 The current density of the conventional HER-OER coupling potential is reduced by 186 mV ( Fig.12 d), and also has excellent catalytic stability ( Fig.12 f), these results all indicate that using urea instead of the anode OER reaction for coupled hydrogen production can not only reduce energy consumption, but also achieve the degradation of urea-rich wastewater and achieve environmental governance; (Linear scan conditions where UOR was tested in 1M KOH containing urea electrolyte, other conditions not specified and Figure 8 same).
[0066] Fig.13 , studied EIS at different potentials in different electrolytes to reveal the relationship between interfacial dynamics, electron transfer and mass transfer during OER and UOR. It can be clearly seen from the EIS graph that when the electrolyte does not contain urea and the voltage is lower than 1.4V, R CT is infinite ( Fig.13 a), which indicates that no reaction occurs in the lower voltage range. The corresponding phase angle in the KOH electrolyte even tends to increase with increasing voltage ( Fig.13 b and 13c). In contrast, the phase angle of the Bode phase diagram in the urea-containing electrolyte decreases continuously with increasing potential ( Fig.13 cf), indicating that the catalyst can react over the entire applied voltage range. This inherently faster chemical kinetics also explains why UOR performs better than OER;
[0067] Fig.14 , studied the structural changes of the prepared catalysts under high pressure and carried out a series of in situ Raman tests. Fig.14a shows the time-dependent in situ Raman diffraction peaks of the catalyst under a fixed voltage. The original catalyst (t = 0 min) shows the initial CoN X and CoO X When a constant voltage is applied (E = 0.925V), V SA -CoN X At about 499 and 573cm -1 The Raman peak corresponding to Co-O(H) is generated at . The contour map also clearly shows that the corresponding peak intensity is gradually increasing, which is consistent with VO X The corresponding Raman peak also appears at 867 cm -1 and tends to be stable over time. X The same test was also performed ( Fig.14 b), at 0 min, CoN X and V SA -CoN X However, although CoN X At 499cm -1 A similar diffraction peak (Co-O(H)) appeared near the V SA -CoN X The above analysis shows that the prepared catalyst material (CoN X and V SA -CoN X )A pre-oxidation process will occur in alkaline electrolytes. The doping of V can effectively promote the pre-oxidation of the catalyst surface, which is beneficial to subsequent reactions.
[0068] After the pre-oxidation process, different voltages were applied to the catalyst to study the phase transition during the actual reaction. Fig.14 c, for V SA -CoN X , when the voltage increases to 1.275 V, 479 and 573 cm -1 The Raman peaks at 461 and 568 cm -1 , indicating the presence of higher valent Co species (CoOOH) on the surface during the reaction, which is consistent with previous studies that the high valent Co species generated in situ under high pressure are regarded as the real active species. -1 The Raman peak at gradually disappears with the increase of voltage, which also explains why the surface V disappears after the stability test under high voltage. Fig.14 d shows the CoN XRaman spectra at different voltages. Obviously, the diffraction peak corresponding to the high-valent Co species appears at 1.325V. CoN X The peak intensity of CoOOH increases with the increase of voltage, 499cm -1 The peak at disappears with the increase of voltage, indicating that CoN X Under high pressure, it undergoes a continuous oxidation process, and the surface is completely converted into high-valent Co species. However, for V SA -CoN X ( Fig.14 c), with the increase of voltage, the intensity of the corresponding peak of CoOOH remains unchanged, indicating that V doping can effectively inhibit the excessive oxidation of Co during the high-voltage reaction. Fig.14 e and 14f are V after UOR stability SA -CoN X TEM and HR-TEM images of CoOOH and CoN X The above analysis results show that V doping can effectively promote the pre-oxidation of catalytic materials in the electrolyte and generate active substances ( Figure 6 g), thus having excellent catalytic activity, in addition, sacrificial surface V can also effectively inhibit the over-oxidation of the catalyst, which always leads to poor activity and stability. In short, V doping promotes the generation of active species and inhibits the accumulation of high-valent species, which makes it possible to achieve excellent catalytic activity and stability under high pressure.
[0069] Fig.15 ,Similar to the OER stability test, after the UOR long-term stability test, an obvious nanosheet region appeared at the edge of the original nanowire of the catalyst. This nanosheet region should be the high-valent Co species (CoOOH) formed in situ during the high-voltage stability test. EDS analysis showed that the element species did not change before and after stabilization;
[0070] Fig.16 , 17, Example 1, the performance test results of Comparative Example 1 show that when 0.3M hydrazine is added to the electrolyte (1M KOH), Example 1 only needs a potential of -0.033V to reach 50mA cm -2 The current density ( Fig.16 a), which is 1.598 V lower than the potential without hydrazine addition ( Fig.16 c). At the same time, Example 1V SA -CoN X When used as cathode and anode to form an electrolyzer for hydrazine-assisted coupled hydrogen evolution, only a potential of 0.0064 V was required to reach 50 mA cm -2 The current density of the conventional HER-OER coupling potential is reduced by 1.572 V ( Fig.16 e). During the stability test, the current density continued to decrease, but it is worth noting that once the electrolyte was refreshed, the current density recovered immediately. This indicates that the decay of the current density is due to the change in the hydrazine concentration in the electrolyte. This also indirectly proves the excellent hydrazine degradation ability of the catalyst ( Fig.16 f). Therefore, the V SA -CoN X The degradation ability of V SA -CoN X The catalyst achieved over 95% hydrazine degradation within 2 hours in both cycles and reduced hydrazine concentration to 6 ppb within 3 hours, exceeding the 10 ppb required by the U.S. Environmental Protection Agency (EPA). Fig.16 h, 16i and 17). These results all indicate that using urea instead of the anode OER reaction for coupled hydrogen production can not only reduce energy consumption, but also achieve the degradation of urea-rich wastewater and achieve environmental governance; (Linear scan conditions where HzOR was tested in an electrolyte containing 1M KOH containing hydrazine, other conditions not specified and Figure 8 same).
[0071] Fig.18 , for Example 1V SA -CoN X The catalyst material was characterized and analyzed after the HzOR stability test. From the SEM, TEM and HR-TEM images before and after the test, the sample V obtained in Example 1 after the stability test SA -CoN X The type and distribution of elements have negligible effects, confirming the stability of this catalytic material under hydrazine oxidation conditions;
[0072] Fig.19 , 20, First, measure V SA -CoN X and CoN X Polarization curves of catalysts in OWS (HER & OER) Fig.19 b) Obviously, V SA -CoN X Only 1.88V is needed to drive 1A cm -2 , which is better than CoN X (1.98V). Of course, the advantage of AEMWE is that it can make good use of renewable energy sources (such as wind and solar energy). Therefore, this type of power fluctuation was simulated to study its response by changing the input voltage and input current in a short period of time. Fig. 20 It can be clearly seen that the catalyst V SA -CoN XWith good response to changes in voltage or current, it also ensures full utilization of renewable electricity.
[0073] Furthermore, UOR is used instead of OER to produce hydrogen. Fig.19 c) at 1A cm -2 This performance difference indicates the absolute thermodynamic advantage of UOR and the broad prospects of UOR-assisted hydrogen production. In addition, to achieve further potential reduction, hydrogen is produced by utilizing HzOR instead of OER coupling. Fig.19 d shows that AEMWE-HzOR only needs 0.21V voltage to reach the ampere current density (1Acm -2 ), the voltage dropped by 1.67 V compared to AEMWE, which is also the lowest voltage reported so far for AEM water electrolysis at ampere current density, which provides a good basis and reference for achieving efficient hydrogen production and wastewater degradation at the same time. Achieving lower voltage at the same current also means lower power consumption, and compared with conventional AEMWE devices, producing the same amount of hydrogen, urea, and hydrazine-assisted AEMWE devices only requires 87.23% and 11.17%, respectively. In addition, at 1A cm -2 At a current density of 1.5 MW, the energy consumption of AEMWE-UOR is only 3.95 kWhNm -3 H2 (equivalent to 43.954 kWh kg -1 H2), the energy consumption of AEMWE-HzOR is only 0.51kWhNm -3 H2 (equivalent to 5.628 kWh kg -1 H2). These are even significantly lower than the energy consumption reported for commercial PEM electrolysers, which are 4.5 to 5.0 kWhNm -3 H2(50.00-55.56kWh kg -1 H2). The cost of producing one kilogram of hydrogen using this AEM electrolyzer is about $0.87 for AEMWE-UOR and about $0.11 for AEMWE-HzOR, which is lower than the US Department of Energy's goal of $1.00 per kilogram of hydrogen by 2030. At the same time, the stability of the AEMWE device, which lasts for more than 200 hours at an ampere current density, also provides a guarantee for its practical application ( Fig.19 e), at the same time, using UOR( Fig.19 f) and HzOR( Fig.19g) It also has excellent stability when replacing OER for hydrogen production, and the increase in voltage is also restored with the renewal of the electrolyte, further proving that it not only has excellent stability and activity, but also has excellent wastewater degradation ability. For AEMWE, AEMWE-UOR, and AEMWE-HzOR, the performance of the three coupled hydrogen production methods is the top level reported so far, even exceeding the current precious metal-based catalysts. In short, this multifunctional, high-performance catalytic material V SA -CoN X It is expected to achieve wastewater treatment while producing hydrogen under various working conditions.
[0074] In summary, this technology has developed a single-atom V-doped CoN X The catalyst not only significantly improved its water splitting performance, but also showed excellent performance in coupled hydrogen production under multiple working conditions. The results showed that the working potentials of OWS, HER-UOR and HER-HzOR were 1.636, 1.450 and 0.0064 V, respectively, to achieve 50 mA cm -2 In particular, in situ Raman analysis shows that sacrificial V at high voltage can effectively promote the generation of active materials while suppressing the accumulation of high-valent Co species, thus providing better activity and stability. SA -CoN X The degradation rate of hydrazine exceeded 95% within 2 h, demonstrating its potential application in wastewater purification. Notably, further testing of the AEM devices showed that only 1.64 V and 0.21 V were required for AEMWE-UOR and AEMWE-HzOR, respectively, to reach an ampere-level current density (1 A cm -2 ), which is also the best performance of AEMWE reported so far. Moreover, its excellent performance and stability provide a guarantee for its real large-scale application implementation. More importantly, the energy consumption of AEMWE-UOR and AEMWE-HzOR is as low as ≈3.953kWh Nm -3 H2 and ≈ 0.506 kWh Nm -3 H2, and the estimated hydrogen production costs are $0.87 and $0.112 per kg H2, respectively. This study provides a new perspective for the design and development of catalysts capable of coupled hydrogen production under multiple operating conditions and is expected to be extended to other catalytic reactions.
[0075] The specification and drawings of the present invention are considered to be illustrative rather than restrictive. On the basis of the present invention, those skilled in the art can make some substitutions and modifications to some of the technical features according to the disclosed technical content without creative labor, all of which are within the protection scope of the present invention.
Claims
1. A multifunctional catalyst V SA -CoN X The preparation method is characterized in that V-Co(OH)2 was prepared by hydrothermal method using metal vanadium source and cobalt source. V-Co(OH)2 was used as precursor and the V-Co(OH)2 precursor was nitrided to prepare multifunctional coupled hydrogen production catalyst V SA -CoN X .
2. The preparation method according to claim 1, characterized in that: 0.1-10mmol Co(NO3)2·6H2O, 1-20mmol CH4N2O, 1-10mmol NH4F, 0.1-10mmol NH4VO3 and 10-50mL deionized water were mixed evenly, and then purified nickel foam (NF) was added, and the mixture was reacted at 100-250°C for 5-20h, and dried in nitrogen atmosphere to obtain V-Co(OH)2 precursor; the obtained V-Co(OH)2 precursor was placed in a tube furnace, and sintered at 300-800°C under nitriding conditions for 1-5h to obtain a multifunctional catalyst V SA -CoN X .
3. The preparation method according to claim 2, characterized in that: The nitrogen source of the nitriding conditions is one of melamine, dicyandiamide, urea and ammonia.
4. The multifunctional catalyst V prepared by the preparation method according to any one of claims 1 to 3 SA -CoN X , characterized in that, The catalyst has a V-doped CoN nanowire structure in morphology.
5. A method for coupled hydrogen production, characterized in that: The multifunctional catalyst V according to claim 4 SA -CoN X It acts as both cathode and anode catalyst in 1M KOH electrolyte to achieve V SA -CoN X Catalyst for hydrogen production by hydrolysis in electrolyzer.
6. A method for coupled hydrogen production, characterized in that: The multifunctional catalyst V according to claim 4 SA -CoN X As cathode and anode catalysts, the cathode electrolyte is 1M KOH and the anode electrolyte is 1M KOH + 0.5M urea, achieving V SA -CoN X The catalyst oxidizes urea at the anode and simultaneously couples the water electrolysis process at the cathode to produce hydrogen.
7. A method for coupled hydrogen production, characterized in that: The multifunctional catalyst V according to claim 4 SA -CoN X As cathode and anode catalysts, the cathode electrolyte is 1M KOH and the anode electrolyte is 1M KOH + 0.3M hydrazine to achieve V SA -CoN X The catalyst oxidizes hydrazine at the anode and simultaneously couples the process of hydrogen production by water electrolysis at the cathode.
8. The method according to any one of claims 5 to 7, characterized in that: The multifunctional catalyst V SA -CoN X The catalytic temperature in the H-type electrolyzer is room temperature and the reaction area is 1 to 5 cm 2 ; The multifunctional catalyst V SA -CoN X The catalytic temperature in the anion exchange membrane electrolyzer is 70°C and the reaction area is 1 to 5 cm 2 .
9. The multifunctional catalyst V as claimed in claim 4 SA -CoN X Application in coupled hydrogen production on anion exchange membrane electrolyzer.